Viruses infecting bivalve molluscs - Renault, Tristan; Novoa, Beatriz (2004)
13 páginas, 5 figuras [EN] Bivalve molluscs are filter feeders and as a consequence they may bioaccumulate in their tissues viruses that infect humans and higher vertebrates. However, there have also been described mortalities of bivalve molluscs associated with viruses belonging to different families. Mass mortalities of adult Portuguese oysters, Crassostrea angulata, among French livestocks (between 1967 and 1973) were associated with irido-like virus infections. Herpesviruses were reported in the eastern oyster, Pacific oyster and European flat oyster and lately in scallops and clams. Disseminated neoplasia, a proliferative cell disorder of the circulatory system of bivalves, although of uncertain aetiology, has been suggested to be caused by retroviral infections. Other viruses described in bivalves are interpreted as members of the Papovaviridae, Togaviridae, Reoviridae, Birnaviridae and Picornaviridae. However, the lack of bivalve cell lines renders difficult virus isolation from molluscs although some viruses can be isolated in fish cell lines. [FR] Les mollusques bivalves sont des filteurs et de ce fait peuvent accumuler dans leurs tissus des virus d'origine anthropique. Par ailleurs, des mortalités ont été constatées chez des bivalves en association à la détection de virus apparentés à différentes familles. Ainsi, les mortalités massives d'huîtres portugaises, Crassostrea angulata, observées en France, de 1967 à 1973, ont été associées à la présence de virus apparentés aux Iridoviridae. Des virus de type herpès ont été détectés chez l'huître américaine, l'huître creuse, l'huître plate, et plus récemment chez la coquille Saint-Jacques et la palourde japonaise. Des néoplasies touchant les cellules circulantes chez les bivalves sont encore aujourd'hui d'étiologie incertaine. Cependant, l'implication de retrovirus dans le processus a été suspectée. Chez les coquillages, d'autres virus ont été décrits et interprétés comme appartenant aux Papovaviridae, Togaviridae, Reoviridae, Birnaviridae et aux ...